Sweden : Report on the Observance of Standards and Codes-Fiscal Transparency and Data Modules-A Note on Recent Developments. (IMF Staff Country Reports; Country Report, 2002)
This technical note focuses on recent developments to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency and Data Modules for Sweden. The authorities are implementing recommendations of the fiscal ROSC module. The government has decided to reform the state audit organization (RRV) as recommended by the report. Effective 2003, the RRV will be transformed from a government agency to an audit office under parliament, staffed by independent officials. The authorities are also following up on recommendations regarding data-related standards and codes.